The Influence of Viable Cells and Cell-Free Extracts of Lactobacillus casei on Volatile Compounds and Polyphenolic Profile of Elderberry Juice - Ricci, Annalisa; Levante, Alessia; Cirlini, Martina; Calani, Luca; Bernini, Valentina; Del Rio, Daniele; Galaverna, Gianni; Neviani, Erasmo; Lazzi, Camilla (Frontiers in Microbiology, 2018)
In this study four strains of Lactobacillus casei, as viable cells or cell-free extracts (CFE), were added to elderberry juice in order to evaluate their effect on phenolic and aromatic profile. Two of them were able to grow in juice while the others showed zero-growth. The same strains were lysed and added as extracts in elderberry juice. Multivariate statistical analysis show a separation among samples containing growing cells, non-growing cells, cell-free extracts, highlighting the particularities of specific strains. Juices added with CFE presented the highest amount of esters. The strains showing growth phenotype, cause an increase of phenyllactic acids. The highest concentration of volatile compounds was observed in strains showing zero-growth, particularly of alcohols, terpenes and norisoprenoids which exhibit typical elderberry notes. Moreover, a significant increase in anthocyanin content was observed in these samples, suggesting the possible use of Lactobacillus for increasing specific molecules, even for non-multiplying bacterial cell.